UNDERSTANDING INDUCTIVE AND DEDUCTIVE APPROACHES IN TEACHING GRAMMAR IN EFL CONTEXT - Hendrikus Male (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2016)
Giving instruction for a language class specifically a grammar class can be a problematic issue of controversy in EFL context for non native speaker (NNS) teacher due to the lack of approach or strategies implementation and the language problem faced in the teaching and learning process. The primary aim of this article is to provide some insight for teachers when conducting or giving instruction to the teaching of English grammar. It also highlights that in giving instruction, combining deductive and inductive approaches can be beneficial for teachers or faculties who are teaching English grammar in the setting of EFL context. Hence, they have to vary the strategies whether it should be extensive or intensive as suggested by Hinkel (2006) in which it might be one of the technique that can be put into account and applied in order to make the teaching of grammar more effective and efficient.Keywords : EFL context, deductive and inductive approaches